Aerospace Structures and Materials - Liu, Yucheng (Frontiers in Aerospace Science ;, 2016)
This comprehensive volume presents a wide spectrum of information about the design, analysis and manufacturing of aerospace structures and materials. Readers will find an interesting compilation of reviews covering several topics such as structural dynamics and impact simulation, acoustic and vibration testing and analysis, fatigue analysis and life optimization, reversing design methodology, non-destructive evaluation, remotely piloted helicopters, surface enhancement of aerospace alloys, manufacturing of metal matrix composites, applications of carbon nanotubes in aircraft material design, carbon fiber reinforcements, variable stiffness composites, aircraft material selection, and much more. This volume is a key reference for graduates undertaking advanced courses in materials science and aeronautical engineering as well as researchers and professional engineers seeking to increase their understanding of aircraft material selection and design.